Development of Hexaquad Robot: Modeling and Framework - Addie Irawan, Hashim; A. R., Razali; Wan Faizal, Wan Ishak; Mohd Rizal, Arshad; Tan, Yee Yin (Asian Research Publishing Network (ARPN), 2015)
This paper presents a proposed reconfigurable multi-legged robot named Hexapod-to-Quadruped (Hexaquad) robot. Reconfigurable legged robot is one of the robotics research area that is generally focused on optimizing the usage of leg during locomotion. Until recent years, most of the researches emphasized on leg reconfigurable design in order to solve the fault tolerant, stability, multi-tasking and energy efficiency. However, the emphasis of the Hexaquad robot is on providing optimum leg usage, actuation configuration as well as satisfying the legged robot stability criterion in reconfiguration mechanism. Inspired from several living creatures, such as insects, crustacean and peristaltic creatures, Hexaquad is designed and modeled to perform flexible spine for leg adjustment and foot-to-gripper transformation. The design also implements the indirect and parallel actuation configuration on leg-joint motion for optimum torque on the joint of each leg without motor/actuator mass affect that commonly happens in multi-limbed system with direct drive configuration. The minimum torque on each joint of the leg is calculated using the static torque calculation on multi-link structure before the actuator/motor is selected, and verification is done by performing fundamental testing on the leg’s movement and standing using direct switching and supply voltage. Further testing and analysis were conducted on the gripper by performing gripping tests using materials of different weight and shape versus total load current on the leg’s actuators. Stress and displacement testing and analysis were also done on the foot-to-gripper (FTG) structure of Hexaquad robot. The results show that the FTG is able to hold 50N forces without any breaking point being detected as well as able to maintain its shape, strength and position upon receiving the forces (surpassing the main objective to lift a 5kg load).